Serological, Culture and Urea Breath Test for Detection of H. Pylori in Gastric Ulcers Patients - Nktel Faaz AL-Saad1 , Nadhim M.H2 , Nawar H.Y2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Helicobacter pylori t is the causative agent of duodenal ulcers and gastric ulcers, thus, it is very importantto determine the most appropriate system used to diagnose it. The current study use invasive and noninvasive process for diagnosis of H. pylori. Culture of H. pylori is one of these invasive systems, and theresults revealed that 35% of specimen was culture positive ( 62.5% in male and 37.5 in female) While, thenon-invasive method like UBT and ELISA IgG and IgA show 67.1% and 71.5% , 29.2% positive resultsrespectively. The distribution of positive test results between male and female by UBT was (41.3%) maleand (58.7%) female) while, the distribution of positive test results between male and female by ELISA IgGand IgA were (61.4%) , (26.3%) in male patients and (78.75%) , (31.25%) in female patients respectively.The results of UBT were increase with age, (34 positive patients in age group 51-60 years old). Serologicaltest of ELISA IgG shows that great % of H. pylori infection (74%) found in patients with group age (41-50)yr.O. and the lowest percentage (39%) was found with age group (< 20 ) years old while, percentages ofpositive cases of ELISA IgA in young age below 20 years old was 79% related to low % with ages increase.